Three-Component Photoredox-Mediated Chloro-, Bromo-, or Iodotrifluoromethylation of Alkenes - Carboni, Aude; Dagousset, Guillaume; Magnier, Emmanuel; Masson, Géraldine (Synthesis, 2015)
A mild and simple three-component procedure for the direct vicinal halotrifluoromethylation of styrenes and aliphatic alkenes has been developed in the presence of [Ru(bpy)3](PF6)2 as a photosensitizer and Umemoto’s reagent as the CF3 source. The multicomponent method offers the advantage of short reaction time, moderate to good yields, and mild reaction conditions.
Keywords: multicomponent reaction; halotrifluoromethylation; photoredox catalysis; halogen; Umemoto’s reagent